COMMON GARDEN OF SEAGRASSES Halodule uninervis (Forsskål) Aschershon AND Halodule pinifolia (Miki) den Hartog - Wagey, Billy Theodorus (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2012)
A simple culture system ‘common garden’ has been set up in Institute of Environmental and Marine Science (IEMS) Dumaguete City Philippines (N 09° 19' 52.8" and E 123° 18' 34.1") at the running seawater outdoor experiment tank aimed to monitor the variation of shoot density, leaf morphology and growth rates of marine plant genus Halodule.  The mean shoot densities of Halodule pinifolia were varied and tend to decrease after the three month period of common garden.   Using one-way ANOVA tests, significant differences were detected on the comparison among the months of common garden (F=6.400; p=0.005), mean leaf growth rate (mm/day) of H. pinifolia (F=13.510; p=0.000), and the mean leaf widths from Siquijor (F=9.274; p=0.001) among the three month period of common garden.  Meanwhile, there were no significant differences detected on leaf width (mm) of H. pinifolia origin from Bantayan site, on mean leaf widths of H. uninervis from Bantayan, on mean leaf widths of H. uninervis from Banilad, and on mean leaf growth rate (mm) of H. uninervis among the three month period of common garden.  The result suggests that the ‘common garden’ procedure could have possibly given a clearer pattern of genus Halodule leaf width, shoot density, and growth rate if the could be prolonged.  It could also be suggested that an adequate number of shoot density on the initial procedure for ‘common garden’ should be properly determined.  This is to avoid overcrowding of the samples later, when growth rate will tend to increase without compromising the leaf width and shoot density measurements. Keywords: common garden, seagrasses, shoot density, leaf width, growth rate, Halodule pinifolia, Halodule uninervis.   Sistem kultur Common Garden sederhana telah dibangun di Institute of Environmental and Marine Science (IEMS) Dumaguete City Philippines (09° 19' 52,8" LU dan 123° 18' 34,1" BT) dalam tangki penelitian di luar ruangan untuk memantau variasi kepadatan tunas, morfologi daun dan laju pertumbuhan rumput laut genus Halodule.  Kepadatan tunas rata-rata Halodule pinifolia bervariasi dan cenderung menurun setelah periode tiga bulan. Menggunakan uji ANOVA satu arah, perbedaan nyata terdeteksi pada pembandingan bulan (F = 6.400, p = 0,005), rata-rata laju pertumbuhan daun (mm/hari) H. pinifolia (F = 13,510, p = 0,000), dan rata-rata lebar daun dari Siquijor (F = 9,274, p = 0,001) antara ketiga bulan common garden.  Sementara itu, tidak ada perbedaan nyata yang terdeteksi pada lebar daun (mm) H. pinifolia asal Bantayan, pada lebar daun rata-rata H. uninervis dari Bantayan, pada lebar daun rata-rata H. uninervis dari Banilad, dan laju pertumbuhan daun rata-rata (mm) dari H. uninervis dalam periode tiga bulan dari common garden. Hasil ini menunjukkan bahwa prosedur 'common garden' mungkin bisa memberikan pola yang lebih jelas tentang lebar daun, kepadatan tunas, dan laju pertumbuhan genus Halodule jika waktu bisa diperlama. Juga dapat disarankan bahwa kepadatan tunas pada prosedur awal common garden harus ditentukan dengan baik untuk menghindari kesesakan sampel di kemudian hari, karena laju pertumbuhan cenderung meningkat sehingga ukuran lebar daun dan kepadatan tunas tidak terpengaruhi. Kata kunci: common garden, lamun, kepadatan tunas, lebar daun, laju pertumbuhan, Halodule pinifolia, Halodule uninervis.